Correction of refractive errors in patients with strabismus. Part II. Clinical aspects of refraction – spectacle and contact lens correction - Tokarz-Sawińska, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
In Part II the clinical aspects of refractive errors such as hyperopia, myopia, astigmatism, anisometropia, aphakia and unilateral pseudophakia have been described along with strabismus and prism and spectacle correction allowing additionally proper visual alignment.